2008
DOI: 10.1166/jnn.2008.185
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Delivery of Quantum Dots to the Cytosol of Live Cells

Abstract: An increasing number of studies have demonstrated the multiple advantages of using nanocrystals, such as Quantum dots, for biological imaging. Quantum dots functionalized with biomolecules on their surfaces were shown to be able to bind to specific extracellular targets via specific recognition and to be internalized inside the cells, thereby allowing the imaging of intracellular pathways. However, the use of Quantum dots for live tracking of intracellular molecules is relatively limited because of the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Cationic liposomes were selected because of their electrostatic interaction with the negatively charged cell membrane, and the OPPC and DOPC+ liposome combination was used primarily in response to published literature that suggested its fusion with the plasma membrane 2,18 as well as our own experiments with the lipofection. 9 Previous results from our lab have shown that cationic liposome fuse with the plasma membrane and release their content into the cytoplasm. This fusion was represented by an increase in plasma membrane after liposome fusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cationic liposomes were selected because of their electrostatic interaction with the negatively charged cell membrane, and the OPPC and DOPC+ liposome combination was used primarily in response to published literature that suggested its fusion with the plasma membrane 2,18 as well as our own experiments with the lipofection. 9 Previous results from our lab have shown that cationic liposome fuse with the plasma membrane and release their content into the cytoplasm. This fusion was represented by an increase in plasma membrane after liposome fusion.…”
mentioning
confidence: 99%
“…This fusion was represented by an increase in plasma membrane after liposome fusion. 9 Figure 3a depicts a fluorescent image and overlay of extracellular labeling of PDGFR protein domains by direct incubation of GPC PDGF cells with T-QDs. The desired e-PDGFR labeling is seen along the cell periphery, and no cytosolic labeling is observed within the plasma membrane.…”
mentioning
confidence: 99%
“…Liposomal QDs show improved shelf life stability and intracellular delivery. 75,76 We have further checked the possibility of intracellular proteins to exert an effect on QD fluorescence. Indeed, in a model solution after incubation at room temperature with BSA, QD fluorescence lifetime decreased ( Figure 9, curve 2 vs 3) and after ∼100 h, the fluorescence was completely quenched (Figure 10).…”
mentioning
confidence: 99%
“…Owing to their hydrophobic surface and potential in vivo toxicity [85,86], the clinical application of QDs is often faced with skepticism. The encapsulation of QDs in liposomes therefore presents an attractive approach to improve QDs' biocompatibility and toxicity [87]. Recently, it was also reported that liposomes consisting of hepatitis B surface antigen and fluorescently labeled polystyrene beads or plasmids were used for tissue and cellular targeting with high specificity [88].…”
Section: Optical Imaging With Liposome-based Nanoprobesmentioning
confidence: 99%